KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING BREAST SELF- EXAMINATION AMONG 2 ND YEAR LADY HEALTH VISITOR STUDENTS IN PUBLIC HEALTH SCHOOLS OF PESHAWAR KHYBER PUKHTOONKHWA PAKISTAN (The Research of Medical Science Review, 2025)
Objectives: To assess knowledge, attitude and practices regarding breast self-examination among LHV second year students in two Public health Schools of Peshawar KPK. Background: Breast cancer is a global health issue and one of the leading cause of death among females around the world. Breast cancer risk factors identification and its control and prevention is necessary to reduce mortality and morbidity among this segment of the population. One of the cheapest methods which do not require money can be helpful in the early detection of breast cancer. This method is known as breast self-examination. Through this method a female can easily detect any abnormality in her breast and can consult a doctor for early management. This method requires nothing but a little time of the female to examine her breast and detect any abnormal change. Methods: This cross-sectional study was conducted in two public health schools of Peshawar from March 2017 to June 2017. A total of eighty LHV students as sample after sample size calculation. Data was collected through well structure and pre-tested questionnaire. The questionnaire were administered among the students got it filled. The data was analyzed through SPSS version 16. Simple frequencies and percentages were calculated of the variables. Results: all the students were females (80). Majority of the students were aware of the general terms regarding BSE. They had no in-depth knowledge about BES. The participants had good positive attitude towards breast self-examination and its techniques. In a total sample of 80, 100% said yes BSE is necessary for detection of abnormality in the breast. Regarding the practice, majority of the students had poor practices. Their comments about the subjective questions were varied and had no in-depth understanding of importance of BSE. Conclusion: The overall knowledge about the general terms of the BSE was good among the students but they had no in-depth knowledge. Majority of the students had very positive attitude towards BSE and its performance. Practices among them were very poor. It is suggested that BSE and its technique may be included in their curriculum and workshops and seminars may be arranged on this important topic periodically.